Multiplicação de mirtileiro (Vaccinium spp.) por estaquia. - Ristow, Nara Cristina (2009)
Blueberry is a temperate fruit species climate, cultivated in Europe, in the United State and Canada, where it has a great economic importance. Its cultivation has driven to a significant expansion in the last years, due to the fruit nutritional characteristics. Blueberries are rich in vitamins and minerals, low calorie and have high antioxidant concentration, establishing a demanding market in healthy foods. The supply of uniform plants with high quality and the development of an efficient and competitive production system added to marketing strategies are among the technologies to be adapted. The objectives of this work were: (i) to determine a suitable substrate to vegetative propagation by microcutting technique and blueberry plant growth; (ii) validate the technique of microcutting; (iii) to evaluate rooting and surviving capacity of blueberry microcuttings. Different experiments were done to achieve the objectives. It was evaluated growth of in vitro-originated plant of cultivar Georgiagem in different substrates. The microcuttings were kept under moist micro-environment conditions at both regulated temperature and light. It was evaluated the blueberry microcutting technique to the cultivars Georgiagem, O‟Neal and Misty under moist micro-environment method, two microcuttings collection period and two IBA concentrations. Was evaluated plant surviving of the cultivars Georgiagem and O‟Neal. Also, it was verified rooting potential of blueberry microcutting treated with different concentrations of indolbutiric acid (IBA) in powder formulation. It was concluded that the substrates such as pinus needle + soil and plantmax®, followed by plantmax® + perlite and rice rull + soil promoted better blueberry plant development of the cv. Georgiagem. The substrates sphagnum peat moss and the mixes of peat + perlite, peat + perlite + coconut fiber and peat + perlite + sawdust allowed higher rooting percentage. The results referent to microcutting rooting, showing high levels of rooting for the cultivars Misty, O'Neal and Georgiagem. The plant surviving of blueberry cultivars O‟Neal and Georgiagem propagated by microcutting method was superior to 90%. The application of 4000 mg/kg of IBA promoted the best rooting rates and root volume of blueberry microcuttings cultivar Climax, showing rooting percentage of 91,67.